Lifestyle brands : a guide to aspirational marketing - Saviolo, Stefania, ....-; Marazza, Antonio, ....- (Houndmills, Basingstoke ; New York, NY : Palgrave Macmillan, 2013)
What do brands like Apple, Diesel, Abercrombie & Fitch and Virgin have in common and what differentiates them from other brands? These brands are able to maintain a relationship with their clients that goes beyond brand loyalty. This gives a complete analysis of Lifestyle Brands, that inspire, guide and motivate beyond product benefits alone.
Keywords: Branding (Marketing).; Consumer behavior; Lifestyles; Merken; Product management